Effect of Material Properties and Strain Rate on Fragmentation of Anisotropic Rock. (13th October 2020) - Wu, R. J.; Li, H. B.
Abstract : In order to investigate the effect of the microproperties of bedding and strain rate on the fragment size distributions of layered phyllite with different bedding dip angles, a split Hopkinson pressure numerical model was established and verified by comparing with the experimental results. A new method to obtain reasonable layered rock dynamic simulation result was proposed. Then, the cumulative distribution curve and average fragment size of layered rocks were calculated after changing the strain rate and microparameters of bedding in the model. The results showed that the samples tend to become pulverized under high strain rate, and it was harder for the samples with low dip angle to be damaged if the bedding shear strength is added, while the fragmentation of high angle samples did not change significantly. Furthermore, the failure of layered specimens was not affected by the tensile strength and stiffness. The wider bedding and narrower space promoted the crack initiation and propagation.